Bhasma : The ancient Indian nanomedicine - Dilipkumar Pal; Chandan Kumar Sahu; Arindam Haldar (Wolters Kluwer Medknow Publications, 2014)
Ayurveda and other Indian system of medicine use metals, but their use is also amply described in Chinese and Egyptian civilization in 2500 B.C. Bhasma are unique ayurvedic metallic/minerals preparation, treated with herbal juice or decoction and exposed for Ayurveda, which are known in Indian subcontinent since 7 th century A.D. and widely recommended for treatment of a variety of chronic ailments. Animal's derivative such as horns, shells, feathers, metallic, nonmetallic and herbals are normally administered as Bhasma. A Bhasma means an ash obtained through incineration; the starter material undergoes an elaborate process of purification and this process is followed by the reaction phase, which involves incorporation of some other minerals and/or herbal extract. There are various importance of Bhasma like maintaining optimum alkalinity for optimum health, neutralizing harmful acids that lead to illness; because Bhasma do not get metabolized so they don't produce any harmful metabolite, rather it breakdowns heavy metals in the body. Methods including for Bhasma preparation are parpati, rasayoga, sindora, etc., Bhasma which contain Fe, Cu, S or other manufacturing process plays a specific role in the final product(s). Particle size (1-2 μ) reduced significantly, which may facilitate absorption and assimilation of the drug into the body system. Standardization of Bhasma is utmost necessary to confirm its identity and to determine its quality, purity safety, effectiveness and acceptability of the product. But the most important challenges faced by these formulations are the lack of complete standardization by physiochemical parameters.